A Study of the Effect Of Dzikr on the Psychology of Students with Disciplinary Problems using Heart Rate Variability (HRV) - Muhammad Nubli, Abdul Wahab; Azham, Abdul Rahman (The International Journal Research Publication's, 2015)
‘Dzikr’ recitation was combined with biofeedback for this experiment. Recitation of ‘dzikr’ (Islamic recitation) is known to have positive impacts towards emotion. When properly recited, ‘dzikr’ could bring calmness to the mind and emotions. An emotion at peace could then bring better results from any actions. Twenty secondary school students with disciplinary misbehavior were chosen to undergo a biofeedback procedure that incorporated ‘dzikr’ recitation. ‘Dzikr’ intervention enabled the students to make changes themselves using the technique of "Heart Rate Variability" (HRV). Students were given technical chanting slowly and loudly of the ‘la ilaha illa Allah’ ‘dzikr’. The study found that students who successfully completed the ‘dzikr’ training were able to make changes within themselves. The students had successfully achieved the change score "HRV Coherence" of the VLF spectrum of LF and HF spectrum conditions. The study had found that this technique was very effective and suitable to be implemented to assist students in making behavioral changes. This technique can be used in schools to improve the effectiveness of the disciplinary problems prevention programs and thus enabling education programs to be implemented successfully.